FABRICATION OF BILAYER STRUCTURE OF NYLON 6 NANOFIBROUS MEMBRANE AND CELLULOSE MEMBRANE FOR WATER MICROFILTRATION APPLICATION - Fauzi, Ahmad
The declining water quality due to harmful pollutant contamination has drawn worldwide concerns because of its negative impacts on human health. This encourages the development of various methods for water purification. Microfiltration membrane is the most used, effective, and efficient water purification method. Nanofibers-based membranes offer some advantages, such as high porosity, low basis weight, high effective surface area, controllable pore size, and continuous-interconnected pores. Those properties allow the membrane to achieve high flux without sacrificing particle rejection. In this study, a bilayer structure of nylon 6 nanofibrous membrane with cellulose membrane has been successfully made for water microfiltration application. The nylon 6 nanofibrous membrane was deposited on a cellulose membrane via the electrospinning technique. The bilayer membrane properties, including mechanical strength, wettability, porosity, and microfiltration performance (flux and rejection) were fully investigated. Those properties were studied using nylon 6 nanofibrous membranes having various fiber diameter and membrane thickness, which were obtained by adjusting the solution concentration and spinning time. The measurement of solution parameters, i.e. viscosity, conductivity, and surface tension, shows a strong relation of solution concentration to those parameters, which later changing the fabricated fiber sizes. The FTIR spectra depicted complete solvent evaporation during and similar nylon 6 functional groups after the electrospinning process. The smaller nanofiber diameter could improve the mechanical strength of the membranes. The porosity test showed a strong relationship between nanofiber diameter to the pore size and pore distribution of the membranes. The contact angle measurement showed a significant influence of the cellulose membrane in increasing the hydrophilicity of the bilayer structure, which then improve the filter flux. The particle rejection test using PSL sizing 308 and 450 nm showed a high rejection (above 98%) for all sample thickness variation. Overall, the bilayer structure of nylon 6 nanofibrous membrane and cellulose membrane showed an excellent and potential ability as microfiltration media.